Khitan Anak Perempuan, Tradisi, dan Paham Keagamaan Islam: Analisa Teks Hermeneutika Fazlur Rahman - Masthuriyah Sa’dan (UIN Raden Mas Said Surakarta, 2016)
The practice of girls circumcision in Indonesian still exists these days. Though it is not as severe as the practice of circumcision in Africa and Middle East, the practice of circumcision in Indonesia is still classified as very unsophisticated: utilizing a small knife and turmeric cut at the tip of the newborn baby clitoris. This practice has been performed hereditary. Merely, in various ways, the construction of gender often cause detriment on female, since there are assumptions and beliefs on female sanctity myth. Yet this practice is very detrimental for female if it is reviewed from the medical, humanity, and social aspects. Ironically, such practice often utilized teological legitimation theorem to strengthen the root of violence against female. Employing Fazlur Rahman’s hermeneutic analysis on double movement theory, this article studied the practice of female circumcision along with tradition and religious interpretation. The result of this study is that the moral ideal aspect of the female circumcision tradition has caused detriment on female whether in medical side or woman’s rights. Subsequently, by legal aspect, the practice of circumcision is only for boys and not for girls.Praktik khitan bagi anak perempuan di daerah Nusantara masih eksis hingga sekarang, meski tidak separah seperti praktik khitan di daerah Afrika dan Timur tengah, praktik khitan di Indonesia masih tergolong sangat sederhana. Dengan menggunakan pisau kecil dan kunyit yang disayat di bibir klitoris bayi yang baru dilahirkan. Praktik tersebut telah berjalan secara turun temurun. Secara sederhana, dalam beberapa bentuk, seringkali konstruksi gender merugikan banyak kaum perempuan, karena adanya asumsi dan kepercayaan tentang mitos kesucian perempuan. Padahal praktik tersebut sangat merugikan perempuan jika ditinjau dari aspek medis, kemanusiaan dan sosial humaniora. Ironisnya, praktik yang demikian seringkali menggunakan dalil legitimasi teologis untuk menguatkan akar kekerasan terhadap perempuan. Dengan menggunakan pisau analisa hermeneutika Fazlur Rahman tentang teori gerak ganda, tulisan ini mengkaji praktik khitan perempuan dengan tradisi dan tafsir keagamaan. Adapun hasil kajian dari tulisan ini adalah bahwa aspek ideal moral dari tradisi khitan perempuan telah merugikan pihak perempuan baik dari segi medis maupun hak asasi perempuan. Kemudian secara aspek legal, praktik khitan adalah untuk anak laki-laki dan bukan kepada anak perempuan.